BIOLOGY AND HOST RANGE OF THE COCONUT LEAFFOLDER, Telicota palmarum MOORE (Hesperiidae, Lepidoptera) - de Pedro , Lorenza B.; Borines, Lucia M.; Gapasin, Dely P. (Annals of Tropical Research, 1990)
The biology and host range of the coconut leaffolder, Telicota palmarum Moore, was studied in the laboratory. The insect underwent five larval instars with an average total developmental period of 35.0 days for males and 35.2 days for females. The males live longer than females with a longevity of 3.9 and 2.4 days, respectively. Fifteen out of 24 plant species tested were fed on by the coconut leaffolder after 24 hrs. Three among the 15 species were further used as food substrate until the insects completed its developmental period. The insect was able to emerge into adults in only one plant, Bunga de China (Adonidiam merrillii Весс).